HUBUNGAN MINAT BACA DENGAN HASIL BELAJAR ILMU PENGETAHUAN ALAM SISWA KELAS V SD SE-GUGUS II KECAMATAN TAMPAN KOTA PEKANBARU - Devi Saparinda; Mahmud Alpusari; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Reading is a way to improve knowledge, expand information and add insight about something that is not yet known. To improve the understanding and mastery of students' learning material, there is a need for interest in reading. The lack of students' interest in reading books can affect students' science learning outcomes. Therefore, the purpose of this research was to find out whether there was a significant relationship between reading interest and science learning outcomes of fifth grade Elementary School in Regional II of Tampan District, Pekanbaru. This research is a type of quantitative research using the correlation method. The subjects in this research were fifth grade students of elementary school in regional II of Tampan District, Pekanbaru. The sample of this researchis 123 students taken randomly using a percentage of the population of 25%. Data collection technique used is a questionnaire that contains students' reading interest and documentation. The data analysis technique using Pearson Product Moment. Based on the results of data analysis it is known that students have moderate reading interest and moderate learning outcomes as well as from the results of the correlation test the rcount obtained is 0,435> rtable is 0,177 and the significance is 0,000 <0,05. Thus, it can be seen that there is a significant relationship between reading interest and sciences learning outcomes of fifth gradeElementary School in Regional II Tampan, Pekanbaru. The degree relationship included in the category is quite strong with coefficient of determination of 18.92%.Key Words: reading interest, science learning outcomes